2010
DOI: 10.1007/s00421-010-1574-8
|View full text |Cite
|
Sign up to set email alerts
|

Relationships among salivary immunoglobulin A, lactoferrin and cortisol in basketball players during a basketball season

Abstract: The aim of this study was to examine the changes and relationships of immune and stress parameters of basketball players during a basketball season. Eight members of National Taichung University basketball team volunteered to participate. Saliva samples were collected at rest and before the start of practice or competition at seven time points during the intense training, competition and recovery period. Salivary immunoglobulin A (sIgA), cortisol, and lactoferrin were measured during training and competition p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
57
2
7

Year Published

2013
2013
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 53 publications
(71 citation statements)
references
References 32 publications
(41 reference statements)
3
57
2
7
Order By: Relevance
“…Mood remained reduced with RSH only. Recent evidence has shown that reduced levels of sIgA and sAA activity indicate attenuated mucosal immune function, especially during periods of intensified training loads and hypoxia (He et al 2010;Li et al 2012;Papacosta and Nassis 2011;Tiollier et al 2005). Therefore, we conclude that mucosal immune function following one session of repeated double-poling sprints in hypoxia or normoxia are similar and, furthermore, that 6 sessions of RSH reduced mood with no signs of impaired mucosal immune function.…”
Section: Discussionsupporting
confidence: 50%
See 2 more Smart Citations
“…Mood remained reduced with RSH only. Recent evidence has shown that reduced levels of sIgA and sAA activity indicate attenuated mucosal immune function, especially during periods of intensified training loads and hypoxia (He et al 2010;Li et al 2012;Papacosta and Nassis 2011;Tiollier et al 2005). Therefore, we conclude that mucosal immune function following one session of repeated double-poling sprints in hypoxia or normoxia are similar and, furthermore, that 6 sessions of RSH reduced mood with no signs of impaired mucosal immune function.…”
Section: Discussionsupporting
confidence: 50%
“…Even without exposure to hypoxia, prolonged highintensity training attenuates sIgA (He et al 2010;Li et al 2012) and enhances the incidence of URTI (Fahlman and Engels 2005;Gleeson et al 1999;Mortatti et al 2012). Interestingly, after a period of high-intensity training, with reduced training load sIgA increases to levels above basal values, thereby substantially lowering the incidence of URTI (Moreira et al 2014).…”
Section: Introductionmentioning
confidence: 92%
See 1 more Smart Citation
“…Kutch et al measured the amount of IgA response to an intense rugby competition among the male adults and observed no considerable change in IgA levels before and after the competition [35]. Hi et al examined the salivary IgA and cortisol levels among the basketball players in a racing season and showed a reverse correlation between salivary cortisol and mucosal immunity of the players, and increase of salivary cortisol level as well as reduction in salivary IgA concentration [36]. These contradictory findings depend on various factors including expression of salivary immunoglobulin A, individual nutrition and exercise and the way exercises are conducted.…”
Section: Discussionmentioning
confidence: 99%
“…Lactoferrin and lysozyme, antimicrobial compounds found in saliva secretions [187,188], have been used to monitor longitudinal changes in elite weightlifters [189] and basketball players [190], measured in endurance exercise in which hydration affects secretion [191], and have been shown to increase in response to running at 75 % VO 2max [192]. Intense exercise, however, may reduce their concentration, which may subsequently increase the risk of infection and incidence of URTIs [83].…”
Section: Other Biomarkersmentioning
confidence: 99%